Kathryn Tanner and the receptivity of Christ and the Church. Issue 2 (May 2022) - Higton, Mike
In conversation with Kathryn Tanner's Christology, I argue that Jesus' receptivity matters. He is who he is, and his story goes the way it goes, only because of what he receives and goes on receiving from all that surrounds him. Similarly, Jesus' church grows and learns by what it encounters in the world. These encounters can be occasions for the work of the Spirit upon it, drawing it into the life that God has established in the world in Jesus. Neither Jesus' incarnate life nor the life of the church should be conceived as involving preservation from creaturely interaction and dependence.